Application of Development Law Theory in Overcoming Legal Voids Related to Land Ownership Restrictions in Indonesia - Febri Jaya; Lu Sudirman; David Tan (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
Considering that housing is a fundamental human need, the fulfillment of adequate housing constitutes a governmental responsibility. This aligns with the mandate of Article 27 paragraph (2) of the 1945 Constitution of the Republic of Indonesia, which guarantees a decent standard of living for all citizens. The government has a responsibility to provide decent housing for all Indonesian people. The absence of legal regulations regarding the limitation of ownership of land rights for residential houses for individuals causes a person to freely and without limits buy a residential house. Through a normative legal study, this research aims to examine the dimensions of the theory of developmental law and its application in addressing legal gaps concerning land ownership restrictions in Indonesia. To answer the problems in this research, the researcher uses a normative type of research with a legal approach to fill the lacuna of existing legal regulations in Indonesia since the object of the research is not yet legally regulated. The findings indicate that the theory of developmental law serves as a highly relevant and appropriate theoretical framework to be further explored and applied in filling the existing legal vacuum related to the study’s object. The problems faced by each individual (especially people of the middle to lower income) to get a decent house are of course the responsibility of the government. This situation is constitutionally mandated under the 1945 Constitution of the Republic of Indonesia. The answers to the problems, the researcher will approach the study by utilizing the approaches, in particular the Welfare State Theory of John Rawls, and the Law Development Theory of Mochtar Kusumaatmadja.